HUBUNGAN STATUS EKONOMI ORANG TUA DENGAN KEMANDIRIAN ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 3 PEKANBARU - Sari, Winta; Indarto, Wusono; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The background of this research is the problem of independence of children aged 5-6 years in TK Negeri Pembina 3 Pekanbaru as there are children who have not been able to do toilet training independently, Still found a child who can not open the pants zipper, there are children who have not Can use “mukena” properly and still assisted by his teacher, still found a child who does not want to tidy up his toys after playing. The purpose of this study is to determine the relationship of economic status of parents with the independence of children aged 5-6 years in TK Pembina 3 Pekanbaru. The method used in this research is quantitative research using correlation technique. The sample used in this study was 93 children. The data collection technique is done by observation sheet. Data analysis technique using scale test and statistic method analysis with SPSS For Windows Ver.22 program. Based on the result of the study of child self-reliance based on the economic status of the parents, 31 people are in high category (33.33%), 47 children with medium category (50.54%), and there were 15 children in the low category (16.13%). Based on hypothesis test results obtained there is a relationship of economic status of parents with independence of children aged 5-6 years in TK Negeri Pembina 3 Pekanbaru. This can be determined from the results of chi square test showing the significance of 0,000 <0.05.Keywords : Economic Status of Parents, Independence